Advances in Crowdsourcing - Garrigos-Simon, Fernando J (Springer, 2015)
​​This book attempts to link some of the recent advances in crowdsourcing with advances in innovation and management. It contributes to the literature in several ways. First, it provides a global definition, insights and examples of this managerial perspective resulting in a theoretical framework. Second, it explores the relationship between crowdsourcing and technological innovation, the development of social networks and new behaviors of Internet users. Third, it explores different crowdsourcing applications in various sectors such as medicine, tourism, information and communication technology (ICT), and marketing. Fourth, it observes the ways in which crowdsourcing can improve production, finance, management and overall managerial performance.